2003
DOI: 10.1002/jcp.10317
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized prostate cancer cells for studying androgen regulated events in cell cycle progression from G1 into S phase

Abstract: Androgen-ablation is a most commonly prescribed treatment for metastatic prostate cancer but it is not curative. Development of new strategies for treatment of prostate cancer is limited partly by a lack of full understanding of the mechanism by which androgen regulates prostate cancer cell proliferation. This is due, mainly, to the limitations in currently available experimental models to distinguish androgen/androgen receptor (AR)-induced events specific to proliferation from those that are required for cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 24 publications
4
48
0
Order By: Relevance
“…5). We reported previously that inhibition of AR activity with Casodex prevents LNCaP cells from entering S phase (22,23). In the present study we observed that Casodex also suppressed TRPM8 expression in LNCaP cells (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…5). We reported previously that inhibition of AR activity with Casodex prevents LNCaP cells from entering S phase (22,23). In the present study we observed that Casodex also suppressed TRPM8 expression in LNCaP cells (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Synchronization of LNCaP cells using isoleucine-free medium was essentially as described by Cifuentes et al (23). Cells arrested in G 0 /G 1 phase were released into complete medium containing 10% FCS and 10 nM testosterone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoleucine deprivation was done by our previously published method (29). The cells were grown to 60% to 70% confluence, and then the medium was replaced with isoleucine-free RPMI 1640 supplemented with 6% dialyzed FCS (Life Technologies), 2.5 mmol/L glutamine, 100 Ag/mL streptomycin, 100 units/mL penicillin, and 10 nmol/L testosterone.…”
Section: Methodsmentioning
confidence: 99%
“…Whole-cell extracts (Cell Lysate ) were incubated with either mAb (mAb 441 ) to a synthetic peptide comprising residues 301 to 317 in the middle of the ATD of AR, pAb (pAb N20 ) to a synthetic peptide comprising residues 1 to 20 of the ATD of AR, or immunoprecipitation buffer lacking antibody (No Ab). The mixtures were then treated with an immunoglobulin adsorbent (proteinblock (29). In these cells, AR levels fluctuated during the cell cycle from a low at G 0 -G 1 (0-4 hours after release from isoleucine block) to a maximum just as S phase begins (12-16 hours after release from isoleucine block; Fig.…”
Section: N-acetyl-leu-leu-norleu (Calpain Inhibitor I or Alln) Additmentioning
confidence: 99%